The behavior of interest rates : an appication of the efficient market model to U.S. treasury bills - Roll, Richard; Samuelson, Paul. (New York : Basic Books Inc. Publishers, 1970)
The purposes of the investigation are to present a formal statement of the efficient market model of security price behavior; to use the theories of term structure of interest rates and efficient market model to derive exact representations of the dynamic behavior of internal rates of return for mono coupon, fixed-maturity bonds; etc
Includes bibliographical references and index.
osc 28/01/2019
Loans
Keywords: Interest rates; Treasury bills